A hybrid experimental and numerical technique for evaluating residual strains/stresses in bonded lap joints. (15th November 2021) - Hassan, Syed Fahad; Kundurthi, Saratchandra; Vattathurvalappil, Suhail Hyder; Cloud, Gary; Haq, Mahmoodul
Abstract: This paper investigates the processing-induced residual strains developed in the adhesive layer of a single lap joint consisting of glass-fiber reinforced polymer (GFRP) adherends bonded with a thermoplastic adhesive, Acrylonitrile Butadiene Styrene (ABS). High-resolution optical fiber sensors were embedded inside the adhesive for in-situ monitoring of strains and temperature during the processing and cooling cycle. The experimental fiber-optic strains are the total strains experienced by the fiber and do not represent the strains in the adhesive because of interfacial effects between the fiber and the adhesive. Hence, a detailed finite element analysis (FEA) model was developed that included the optical fiber within the bondline. The experimentally measured optical fiber strains were first used to calibrate the FE models at each cooling rate. These FE models were then used to predict residual strains and stresses in the bulk adhesive. The FE models showed that the strains calculated along the optical fiber provided a close approximation to the actual strains experienced by the ABS adhesive around it at the center of the overlap region. The experimental technique, with appropriate post-processing, can be used to get a reliable first-hand approximation of the residual strains induced in the bulk adhesive during curing/processing. A critical conclusion from the FE investigation is that, for all cooling rate cases, the von-Mises residual stresses generated inside the bulk ABS adhesive ranged between 65 and 80% of its tensile strength, which showcases the importance of processing-induced residual stresses and their effects on safety-critical components like bonded joints. The hybrid FE-experimental approach used in this work can be extended to other joint geometries and material configurations.